Approach temperament across cultures: Validity of the Infant Temperament Scale in MAL-ED. Issue 4 (2nd October 2018) - Pendergast, Laura L.; Jones, Paul; Scharf, Rebecca; Rasheed, Muneera; Schaefer, Barbara A.; Murray-Kolb, Laura E.; Rasmussen, Zeba; Svensen, Erling; Tofail, Fahmida; Seidman, Jessica C.; Caulfield, Laura E.; The MAL-ED Network Investigators,
ABSTRACT: Characteristics of temperament have been shown to predict aspects of personality and psychopathology. Approach temperament (i.e., sensitivity, reactivity, and behavioral disposition toward reward stimuli) may be a particularly salient predictor of developmental outcomes (e.g., Nigg, 2006; Shiner & Caspi, 2003). However, there is little research on approach temperament among children from low- and middle-income nations. This study examined the validity of an adapted version of the Infant Temperament Scale across eight international sites with a focus on approach temperament. Our sample included 1, 933 infants from eight study sites in low- and middle-income nations: Bangladesh, Brazil, India, Nepal, Peru, Pakistan, South Africa, and Tanzania. The Infant Temperament Scale was translated and administered as a structured interview to caregivers at each site. Exploratory and confirmatory factor analyses were used to examine the factor structure of the scale, and multiple indicator multiple cause (MIMIC) modeling was used to examine invariance of scores across sites. The findings supported the validity of an approach temperament factor. Although the findings did not support the cross-cultural use of the entire Infant Temperament Scale among individuals from low- and middle-income nations in our sample, the supported approach temperament factor is a theoretically important subconstruct. Moreover, the inability to measure other aspects of temperament across cultures may have important implications for researchers interested in the nature of temperament. Implications and future directions are discussed.